2021
DOI: 10.1017/s0022215121002139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lifestyle modifications on snoring and mild sleep apnoea patients

Abstract: Objective Behavioural modification through increasing nutritional awareness, along with customised dietary changes and education about physical inactivity, for obese snorers and mildly sleep apnoeic patients would help improve their quality of life. Methods A one-year prospective interventional study enrolled snorers and/or mild obstructive sleep apnoea sufferers, with 36 patients each in the test group and control group. Nutritional information and tailor-made diet charts were given to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Some studies, 18,19 but not others, 20,21 have suggested that weight reduction has a positive impact on obstructive sleep apnea (OSA) outside of pregnancy 22 . One study suggested that awareness of basic nutrition and customized diet plans are associated with improved sleep and reduced snoring 23 . The occurrence of sleep‐disordered breathing is higher during pregnancy compared with non‐pregnant individuals, 24 yet few intervention studies have been reported 25,26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies, 18,19 but not others, 20,21 have suggested that weight reduction has a positive impact on obstructive sleep apnea (OSA) outside of pregnancy 22 . One study suggested that awareness of basic nutrition and customized diet plans are associated with improved sleep and reduced snoring 23 . The occurrence of sleep‐disordered breathing is higher during pregnancy compared with non‐pregnant individuals, 24 yet few intervention studies have been reported 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“… 22 One study suggested that awareness of basic nutrition and customized diet plans are associated with improved sleep and reduced snoring. 23 The occurrence of sleep‐disordered breathing is higher during pregnancy compared with non‐pregnant individuals, 24 yet few intervention studies have been reported. 25 , 26 A recent meta‐analysis 27 showed an increased risk of snoring, short sleep duration and poor sleep quality among pregnant women with high BMI; however, most of the studies included were conducted late in gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Jonathan Fishman and Edward Fisher Although the need for treatment of moderate or severe obstructive sleep apnoea (OSA) is established, treatment of mild OSA is controversial, and is generally managed with simple lifestyle measures, with consideration given to a dental appliance. 1 It is difficult to justify subjecting patients with mild OSA to extensive treatment, especially when there is no conclusive impact of treatment on patients' morbidity and mortality. However, if it is proven that mild OSA progresses to moderate or severe OSA, this then raises the need for a different approach in managing mild OSA.…”
mentioning
confidence: 99%